THE QUALITY OF LIFE OF STUDENTS WHO STUDY IN UKRAINE AND POLAND - Olga Andriychuk; Vasyl Pantik; Volodymyr Kovalchuk; Serhii Savchuk (Lesya Ukrainka Volyn National University, 2017)
The current relevance of the research. The study of the quality of life is a core issue both at the scientists' level and the level of government workers in the world. The main goal is not only to extend lifetime, but to improve its quality too. Ukraine's desire to enter the European Community and the European Union is impossible without substantial improvement of the quality of life. However, the quality of life depends on the quality of labor potential, and hence on the prospects for the development of the country. Since the 70s of the XXth century, the state of the quality of life has begun to attract the attention of many researchers and practitioners in various fields of researches. The Council of the European Union adopted a development strategy in 2010 - 'Europe 2020: A Strategy for smart, stable and inclusive growth' based on the analysis of monitoring the quality of life of the European Union. The aim was to study the students' components of the quality of life, depending on the place of study (countries) and the origin (nationality). Methods: synthesis and analysis of the current scientific and methodological studies on self-assessment of the quality of life using the SF-36 questionnaire and the methods of mathematical statistics. Results. Analyzing the students' answers, we revealed the regularity among indicators of the physical and mental (psychological) components of the quality of life and the sex of the respondents, the year of study, self-evaluation of their study achievements, conditions of life. Besides, the main components that play the leading roles in shaping the overall picture of the quality of life and those that reduce the quality of students' lives were found out. Due to the analysis of the correlations between indicators of the physical and mental (psychological) components of the quality of life, the interdependent components that form the basis of the students' quality of life were highlighted. Conclusions. The study makes it possible to compare both the generalized results of the quality of the Ukrainian and Polish students' lives and the individual components that form the physica l and mental (psychological) basis for the quality of life.